Plan de Proyecto para el Diseño del Plan de Gestión de Riesgos Operativos y su aplicación en un caso práctico en el Centro de Atención Integral de Clientes de Heredia (CAICH-ICE). - Orlich-Solano, David; Thompson-Briceño, Ivannia (Instituto Tecnológico de Costa Rica, 2011)
Given the need and importance of providing quality service to customers, the Instituto Costarricense de Electricidad (ICE) should ensure the needs of the info-communications services demand, provide customer service in a timely manner and ensure quality and continuity of services provided. Comprehensive Care Customer Centers (Centro de Atención Integral al Cliente de Heredia CAICH in Spanish) are the representatives of the ICE in different areas where it offers services, and are the ones who must ensure a service that complies and meets the needs of the customers. When performing an analysis of the problematic at the CAICH operational management level, issues are identified. Unaccomplished processes, and an increase in the execution times of activities, generating delays in the operational value chain and rework unconformities at operational and customers level (internal and external customers). This represents the final breach in the operational objectives. After identifying the problematic and the need of providing quality and competitive services, strategies are defined to improve the CAICH operational management. The main objective of this project is to develop the project plan for designing the Operational Risk Management Plan for the CAICH by using the methodological framework of PMBOK ® to improve the CAICH operational management and reduce the negative impact on quality service and customer image. The design of the Operational Risk Management Plan is based on the expertise of the staff of the four level two functional strategic processes of the CAICH, with the aim of using the most accurate and appropriate information and knowledge for the effective operational risk analysis.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2011
Keywords: Gestión del tiempo; Reducción de costos; Gestión de riesgos; Comunicaciones; Investigación; Gestión de calidad